Imaging the uptake, distribution and metabolism of agrochemicals using MALDI mass spectrometry imaging - Kubicki, Michael (Technische Universität Dortmund, 2022)
Agrochemicals such as fungicides, herbicides, or insecticides are widely used worldwide to control weeds, pests, and diseases to reduce the loss in crop production and increase yield and quality of crop products. Successful control and safe usage of these types of compounds depend on the compound reaching the target site within the crop plant. Therefore, monitoring agrochemical distribution within plant tissues delivers significant insights into agrochemicals adsorption, distribution, metabolism, and elimination (ADME). In the present dissertation, matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI) has been used to examine the uptake and distribution of a range of agrochemicals into a various number of crop plants and to complement their results with conventional methods such as autoradiography, liquid scintillation, and HPLC-MS. The uptake, distribution, metabolic behavior, and the nature of the residue of selected fungicides, herbicides and insecticides was investigated and delivered spatial information about the uptake and systemicity of the agrochemicals within the plants.
Keywords: MALDI imaging; Environmental science; Plant protection; Pesticide; 540; Matrix-unterstützte Laser-Desorption; Umweltforschung; Pestizid